2004
DOI: 10.1021/ja0471525
|View full text |Cite
|
Sign up to set email alerts
|

Copper(I)-Catalyzed Synthesis of Azoles. DFT Study Predicts Unprecedented Reactivity and Intermediates

Abstract: Huisgen's 1,3-dipolar cycloadditions become nonconcerted when copper(I) acetylides react with azides and nitrile oxides, providing ready access to 1,4-disubstituted 1,2,3-triazoles and 3,4-disubstituted isoxazoles, respectively. The process is highly reliable and exhibits an unusually wide scope with respect to both components. Computational studies revealed a stepwise mechanism involving unprecedented metallacycle intermediates, which appear to be common for a variety of dipoles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
949
1
25

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,586 publications
(1,004 citation statements)
references
References 24 publications
29
949
1
25
Order By: Relevance
“…Since the early reports, a variety of transition-metal catalysts have been used for the reactions between mono-or disubstituted alkynes and azides (vide infra). For the Cu(I) catalyzed reaction, a variety of mechanisms involving Cu(I)-aryl intermediates have been proposed in which the key-step species contains either mononuclear [35] or binuclear copper species [30][31][32][33][34][35][36][37][38]. Theoretical studies of the RuAAC reaction have also been reported [28,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Since the early reports, a variety of transition-metal catalysts have been used for the reactions between mono-or disubstituted alkynes and azides (vide infra). For the Cu(I) catalyzed reaction, a variety of mechanisms involving Cu(I)-aryl intermediates have been proposed in which the key-step species contains either mononuclear [35] or binuclear copper species [30][31][32][33][34][35][36][37][38]. Theoretical studies of the RuAAC reaction have also been reported [28,[39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Cycloaddition reactions are a valuable strategy to access highly functionalized structures owing to their experimental ease, good synthetic yields, and compatibility with multiple functional groups,38 with the alkyne–azide 1,3‐dipolar Huisgen cycloaddition39 being one of the most widely used reactions in chemical biology. This strategy was utilized by Fairfull‐Smith and co‐workers to conjugate azidocoumarin derivatives to an alkyne‐containing isoindoline nitroxyl in a copper‐catalyzed azide–alkyne cycloaddition (CuAAC) process to generate fluorophores with high sensitivity to oxidative processes (Figure 6 A) 40.…”
Section: Cycloaddition Reactions In Fluorescent Probe Developmentmentioning
confidence: 99%
“…The corresponding formation of a N-alkyl-or aryltriazolyl copper species has been previously investigated. [15] Although the involvement of more than one copper might be possible, a mononuclear copper acetylide with one pyridine spectator ligand on copper was chosen as a starting point as our interest is in comparing the reactivity of N-sulfonyl azide to Nalkyl analogues (X1, Figure 3). For methanesulfonyl azide (X4) used in this study, the overall barrier for the formation of metallacycle (X3ts) was calculated at 57 kJ mol À1 .…”
Section: Computational Calculationsmentioning
confidence: 99%